Keputusan Pembelian melalui Live Streaming E-Commerce Shopee, Online Customer Review, dan Free Gift (Studi Kasus pada Pelanggan MS Glow by Mirza) - Monica, Sevi; Jannah, Miftahul (Jurnal Kajian Ilmu Manajemen (JKIM), 2024)
This research aims to determine the influence of Shopee e-commerce live streaming, online customer reviews, and free gifts on purchasing decisions for MS Glow by Mirza. The research method uses quantitative methods. The data used are primary and secondary data. Data was obtained by distributing questionnaires to a sample of 100 respondents. This research uses a purposive sampling method and the analytical tool used is multiple linear regression with the help of the SPSS 29 program. Partial test results show that live streaming has a significant influence on purchasing decisions, online customer reviews have no significant influence on purchasing decisions, and free gifts have no significant influence on purchasing decisions. For simultaneous tests, it shows that live streaming, online customer reviews, and free gifts have a significant influence on purchasing decisions. The coefficient of determination value is 0.665, meaning that the regression model obtained is able to explain that the variables live streaming, online customer reviews, and free gifts can influence purchasing decisions for MS Glow by Mirza products by 66.5%. Meanwhile, the remaining 33.5% is influenced by other variables not explained in this research.